KARAKTERISTIK PENDERITA KANKER PARU YANG DIRAWAT INAP DI BANGSAL PARU RUMAH SAKIT UMUM DR. SOEDARSO PONTIANAK PERIODE 1 JANUARI 2006 31 DESEMBER 2010 - ., Rhomadon Apdani (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Lung cancer is malignant tumor which come from epithels of bronchus, bronchiolus, and alveolus. The purposes of this research are to know characteristics lung cancer according to age, sex, symptoms, result of anatomical pathology test, and Case Fatality Rate (CFR).Method: This research is a descriptive with cross-sectional design. Consecutive sampling is used to determine object by collecting data from hospital medical record. The data is processed by using Statistical Product and Service Solution (SPSS) 17.Result: The results of this research find 43 patients of lung cancer. The characteristics are age ? 40 years is 33 patients (76,7%), age < 40 years is 10 patients (23,3%); sex: male is 33 patients (76,7%), female is 10 patients (23,3%); symptoms: dyspnea is 23 patients (53,5%), cough is 18 patients (41,8%), hemoptysis is 13 patients (30,2%), chest pain is 16 patients, other is 6 patients (14%); anatomical pathology test: adenocarcinoma is 25 patients (58,1%), large cell carcinoma is 18 patients (41,9%); CFR in 2006 is nothing beacuse no patient, in 2007 is 66,7%, CFR in 2008 is 18,7%, CFR in 2009 is 15,4%, CFR in 2009 is 12,5%, CFR in 5 years is 23,3%.Conclusion: The research results show major proportion; age is ? 40, sex is male, symptom is dyspnea, anatomical pathology test is adenocarsinoma, and CFR is in 2007.Keywords: Lung Cancer; Age; Sex; Symptoms; Anatomical Pathology; CFR